LITERASI MATEMATIKA SMA DENGAN PROBLEM BASED LEARNING BERBANTUAN MODUL - Khumairoh, Herlina Milatina; Sukestiyarno, Sukestiyarno; Agoestanto, Arief (Universitas Bhinneka PGRI, 2024)
Mathematical literacy is an important skill that students need in learning mathematics. The Problem Based Learning model invites students to be able to solve existing problems to improve students' mathematical literacy. The purpose of this study was to determine the mathematical literacy of SMA N 1 Grabag students during learning by using the Problem Based Learning model assisted by modules. The research method used was quantitative research method. This research design uses Pretest - Posttest Control Group Design. The population in this study were all X grade students at SMA N 1 Grabag totaling 9 classes. Sampling in this study used cluster random sampling and obtained an experimental class, namely class X E5 with 36 students and a control class, namely class X E6 with 35 students. The data collection method used the mathematical literacy test method. The statistical analysis used normality test, homogeneity test, independent sample t test, and one party t test.